Fixation Technique Using PLLA Pins Gives Good Clinical Results Regardless of Bone Condition in Osteochondral Lesion of Talar Dome. Issue 4 (16th October 2019) - Nakasa, Tomoyuki; Ikuta, Yasunari; Tsuyuguchi, Yusuke; Ota, Yuki; Kanemitsu, Munekazu; Adachi, Nobuo
Category: Ankle Introduction/Purpose: Osteochondral lesion of the talus (OLT) has various treatment options which are chosen depending on the stage, size and cartilage condition. The fixation technique can restore the natural congruency with the hyaline cartilage. However, it is not clear whether a bone condition such as the disruption of the subchondral bone plate will affect the clinical results after the fixation of the osteochondral fragment. We hypothesized that even if the subchondral bone plate were disrupted, if the articular cartilage condition in the osteochondral fragment were good, then the clinical results of the fixation technique would be good. The aim of this study was to explore whether the fragment's bone condition affects clinical outcomes including second look arthroscopy. Methods: Eighteen ankles in 17 patients, which had undergone the fixation technique using poly-L-lactide (PLLA) pins, were included. The mean follow-up period was 18.8±8.9 months. They consisted of 10 males and 7 females, with a mean age of 20.1±10.1 years. Based on the fragment's bone condition on preoperative CT, ankles were divided into 3 groups; normal, segmentation, and absorption groups. The American Orthopaedic Foot & Ankle Society (AOFAS) score were evaluated both pre and post surgery. On MRI, the BME area was measured, and stability, incorporation, subsidence, and the surface of the articular cartilage of the fragment were evaluated. Second look arthroscopic findings were evaluated in 13 ankles. The repair of OLT was assessed according to the criteria of the ICRS which are allocated for the degree of filling defect by repair tissue, integration, and surface appearance of the repair site. Results: The AOFAS score before surgery significantly improved from 72.1±2.8 points to 98.6±3.3 points at the final follow-up in all ankles. In each group, the AOFAS score improved and there were no significant differences in AOFAS score among the 3 groups at final follow-up. MRI at 1 year showed good incorporation and cartilage surface in all groups, but the bone marrow lesion in the absorption group was significantly larger than that in the other groups. In the second look arthroscopic findings, the ICRS scale for the normal, segmentation, and absorption groups produced 10.6±1.7 points, 9.8±1.9 points, and 10.7±1.2 points, respectively. Conclusion: Good clinical results including those of second look arthroscopy for osteochondral fragment fixation using PLLA pins in OLT were obtained, even in the case of disruption of the subchondral bone plate. Since the fixation procedure can restore the native contour of the articular cartilage surface, this surgical procedure is a viable option for large OLT lesions regardless of bone condition in the osteochondral fragment.